2016
DOI: 10.1371/journal.pone.0157270
|View full text |Cite
|
Sign up to set email alerts
|

Expression and the Peculiar Enzymatic Behavior of the Trypanosoma cruzi NTH1 DNA Glycosylase

Abstract: Trypanosoma cruzi, the etiological agent of Chagas’ disease, presents three cellular forms (trypomastigotes, epimastigotes and amastigotes), all of which are submitted to oxidative species in its hosts. However, T. cruzi is able to resist oxidative stress suggesting a high efficiency of its DNA repair machinery.The Base Excision Repair (BER) pathway is one of the main DNA repair mechanisms in other eukaryotes and in T. cruzi as well. DNA glycosylases are enzymes involved in the recognition of oxidative DNA dam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 94 publications
(126 reference statements)
0
14
0
Order By: Relevance
“…While lipids and proteins may be re-synthesized DNA damage have to be repaired [10][11][12] mainly by the DNA Base Excision Repair (BER) pathway. [13][14][15][16] BER is a highly conserved pathway in eukaryotes that begins with the recognition of the oxidized base by one of many DNA glycosylases, which remove the damaged base, generating an AP site that is recognized by an apurinic/apyrimidinic endonuclease (AP endonuclease). This enzyme cleaves the DNA strand resulting in the formation of a one-nucleotide gap flanked by 3′-hydroxyl and 5′-deoxyribosephosphate (5′ dRP) ends.…”
mentioning
confidence: 99%
“…While lipids and proteins may be re-synthesized DNA damage have to be repaired [10][11][12] mainly by the DNA Base Excision Repair (BER) pathway. [13][14][15][16] BER is a highly conserved pathway in eukaryotes that begins with the recognition of the oxidized base by one of many DNA glycosylases, which remove the damaged base, generating an AP site that is recognized by an apurinic/apyrimidinic endonuclease (AP endonuclease). This enzyme cleaves the DNA strand resulting in the formation of a one-nucleotide gap flanked by 3′-hydroxyl and 5′-deoxyribosephosphate (5′ dRP) ends.…”
mentioning
confidence: 99%
“…TcFEN1 is found in aggregates in the nucleoplasm. In previous work, we have shown that using pTREXgfp control vector, the expression of the green fluorescent protein remains in the cytoplasm [Sep ulveda et al, 2014;Ormeño et al, 2016]. The subcellular localization of TcFEN1 was maintained when the parasites were treated with H 2 O 2 (not shown).…”
Section: Expression and Activity Of Purified Recombinant His-tcfen1-gmentioning
confidence: 83%
“…Transfected epimastigotes over‐expressing HIS‐TcFEN1‐GFP maintained in the exponential phase of growth were exposed to a sustained H 2 O 2 production using the glucose/glucose oxidase system [Sepúlveda et al, ; Ormeño et al, ] for 2 (Fig. A) and (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations